Melting Phenomenon in a Squeezed Rheology of Reactive Rate Type Fluid - Ahmad, Shakeel; Farooq, Muhammad; Rizwan, Muhammad; Ahmad, Babar; Rehman, Saif Ur (Frontiers in Physics, 2020)
The present study concentrates on squeezed unsteady magneto-hydrodynamic flow of Jeffrey fluid confined between two infinite parallel plates. Description of heat transfer process is disclosed through melting and thermal radiation effects. Features of viscous dissipation are also incorporated. Characteristics of mass transport are explored with chemical reaction. Modulated nonlinear partial differential equations are reduced by implementing appropriate transformations. Approximate convergent solutions are calculated through analytical technique. Characteristics of velocity, concentration and fluid temperature are illustrated graphically and also discussed comprehensively in physical. Skin friction co-efficient and Nusselt number are sketched and discussed through graphs. It is noticed that horizontal velocity component and temperature of Jeffrey liquid are dominant for greater melting parameter. Moreover, temperature field decays for dominant thermal radiation parameter.